Simultaneous estimation of silodosin and silodosin β-D-glucuronide in human plasma using LC-MS/MS for a pharmacokinetic study. Issue 4 (4th July 2018) - Yadlapalli, Siva Sankara Rao; Katari, Naresh Kumar; Manabolu, Surendra Babu; Ravi, Vasu Babu
ABSTRACT: A rapid, simple, sensitive and selective LC-MS/MS method has been developed and validated for simultaneous quantification of silodosin and silodosin β-D-glucuronide human plasma using stable labelled isotopes as internal standards. Solid phase extraction technique (SPE) was used for the extraction and the method validated over a range of 0.20 ng/mL to 100.56 ng/mL for silidisin and 0.20 ng/mL to 101.63 ng/mL for silodosin β-D-glucuronide. The chromatographic separation was achieved on Cosmicsil Adze C18 (4.6 × 100 mm, 3 µm) column using a mobile phase consisting of acetonitrile, methanol and 10 mM ammonium acetate buffer 50:20:30 (v/v/v) at a flow rate of 1.000 mL/min with run time of 4 min. The API-4500 LC-MS/MS was operated under the multiple-reaction monitoring mode using electrospray ionization. The developed assay method was successfully applied to a pharmacokinetic study in humans.